Intervention fidelity in participatory research: a framework. Issue 1 (1st January 2020) - Trickett, Edison; Rasmus, Stacy M.; Allen, James
ABSTRACT: In community interventions more generally, the concept of fidelity refers to the degree to which a program is delivered as intended. The present paper discusses ways in which fundamental aspects of participatory research challenge the concept of fidelity and differ from more traditional science-dominated approaches. We begin with a discussion of the fidelity concept and some of its strengths and limitations. We then discuss both social problems and proposed solutions as representing complex problems defying simple or permanent solutions. We suggest that three prominent aspects of participatory research highlight this complexity and pose challenges in assessing fidelity. First, in participatory research, the goal is not only scientific but also social action on a local issue as well. Second, the participatory process among varied partners is itself part of the intervention itself to be understood as affecting both processes and outcomes. Third, the goals of participatory research include community-level as well as individual-level changes. These issues are illustrated in a discussion of how culture is conceptualized and acknowledged in fidelity assessment. We conclude with some recommendations for approaching fidelty in participatory research in a way that appreciates its differences from more traditional paradigms underlying community interventions.